Model Layanan Konseling Kelompok Islami dengan Teknik Modeling untuk Meningkatkan Kecerdasan Emosi Siswa - Sultan, Ana Dhiqfaini; Fitriani, Ana; Wulandari, Ratna (JURNAL KONSELING GUSJIGANG, 2023)
Purpose of the research is develop a product in the form of a model of Islamic group counseling with modeling techniques that can improve emotional intelligence of students. The development of a model of Islamic group counseling is carried out by providing assistance carried out by counselors to students through group situations which in practice are given an understanding of Islamic values in the Al-Qur'an and hadith. With this treatment, it is possible for each member of the group to show their active participation in order to support the mindset and experience of group members. The research design used in this study is a Quasi Experimental Design, and uses the Non Equivalent Control Group Design model. In conducting this research, 2 groups were used, namely the control group and the experimental group. The research results show that the implementation of Islamic Group Counseling using Modeling Techniques can significantly increase students' emotional intelligence. In the control group, an increase in emotional intelligence was obtained from students who were given treatment of 67.5%. Based on the results of the Wilcoxon signed rank test, Pvalue  µ  (0.012 0.05).